Multiband optical variability of the TeV blazar PG 1553 + 113 in 2019 - Dhiman, Vinit; Gupta, Alok C; Kurtanidze, Sofia O.; Eglitis, I; Strigachev, A; Damljanovic, G; Wiita, Paul J; Gu, Minfeng; Gaur, Haritma; Vince, Oliver; Bachev, R; Bisen, D P; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We report the flux and spectral variability of PG 1553 + 113 on intra-night (IDV) to short-term time-scales using BVRI data collected over 91 nights from 28 February to 8 November 2019 employing 10 optical telescopes: three in Bulgaria, two each in India and Serbia, and one each in Greece, Georgia, and Latvia. We monitored the blazar quasi-simultaneously for 16 nights in the V and R bands and 8 nights in the V, R, I bands and examined the light curves (LCs) for intra-day flux and colour variations using two powerful tests: the power-enhanced F-test and the nested ANOVA test. The source was found to be significantly (>99 per cent) variable in 4 nights out of 27 in R-band, 1 out of 16 in V-band, and 1 out of 6 nights in I-band. No temporal variations in the colours were observed on IDV time-scale. During the course of these observations the total variation in R-band was 0.89 mag observed. We also investigated the spectral energy distribution (SED) using B-, V-, R-, and I-band data. We found optical spectral indices in the range of 0.878 ± 0.029 to 1.106 ± 0.065 by fitting a power law (Fν∝ν−α) to these SEDs of PG 1553 + 113. We found that the source follows a bluer-when-brighter trend on IDV time-scales. We discuss possible physical causes of the observed spectral variability.
Online veröffentlicht 2022 December 20
Gesehen am 24.04.2023